Long-term Oxygen Treatment in Chronic Obstructive Pulmonary Disease: Recommendations for Future Research: An NHLBI Workshop Report - Croxton, Thomas L; Bailey, William C; NHLBI Working Group on Long-term Oxygen Treatment in COPD (American journal of respiratory and critical care medicine, 2006)
Long-term oxygen treatment (LTOT) prolongs life in patients with chronic obstructive pulmonary disease (COPD) and severe resting hypoxemia. Although this benefit is proven by clinical trials, scientific research has not provided definitive guidance regarding who should receive LTOT and how it should be delivered. Deficiencies in knowledge and in current research activity related to LTOT are especially striking in comparison to the importance of LTOT in the management of COPD and the associated costs. The National Heart, Lung, and Blood Institute, in collaboration with the Centers for Medicare and Medicaid Services, convened a working group to discuss research on LTOT. Participants in this meeting identified specific areas in which further investigation would likely lead to improvements in the care of patients with COPD or reductions in the cost of their care. The group recommended four clinical trials in subjects with COPD: (1) efficacy of ambulatory O(2) supplementation in subjects who experience oxyhemoglobin desaturation during physical activity but are not severely hypoxemic at rest; (2) efficacy of LTOT in subjects with severe COPD and only moderate hypoxemia; (3) efficacy of nocturnal O(2) supplementation in subjects who show episodic desaturation during sleep that is not attributable to obstructive sleep apnea; and (4) effectiveness of an activity-dependent prescription for O(2) flow rate that is based on clinical tests performed at rest, during exercise, and during sleep.